Finding and keeping a mentor: a year of reflection - Sarah Cottrell-Cumber (Trauma Surgery & Acute Care Open)
I had the privilege to learn from Dr Sharon Henry, the American Association for the Surgery of Trauma (AAST) vice president, over the past year as the AAST Associate Membership Mentoring Scholarship recipient. This essay serves as a reflection on my year and was presented at the 2024 AAST Annual Meeting. Mentorship breaks down into two stages: finding a mentor and keeping a mentor. Finding a mentor can occur through a formal mentorship process or relationships formed organically. It takes a connection between two people and time for a relationship to form. Keeping a mentor takes effort and intentionality. Mentorship doesn’t end when the scholarship does. It is fluid, without direction, without a timeline, and it will evolve. It will take effort and intention to keep a mentor, but the reward is so great for all that effort put in. Often, what we receive out of mentorship cannot be quantified but the impact is profound.